Covalent Organic Frameworks for Immunoassays: A Review - Suling Yang; Hongmin Liu (Biosensors)
Immunoassays relying on highly specific antigen–antibody recognition are important tools for effectively measuring the levels of various targets. Efforts have been made in the development of various methods to improve the detection sensitivity and stability of immunoassays. Covalent organic frameworks (COFs), as an emerging class of novel crystalline porous materials, have unique advantages such as flexible designability, high surface area, excellent stability, tunable pore sizes, and multiple functionalities. They have great potential as novel sensory materials. Herein, we summarize the advances of COFs in electrochemical and optical immunoassays serving as electrode modifiers, signal indicators, enzyme or probe carriers, etc. Meanwhile, the design and application of typical COFs-based immunoassays in the determination of different targets are discussed in detail. Finally, challenges and future perspectives are presented.